2010
DOI: 10.1017/s1751731109991431
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for resistance to trichostrongylid infection in dairy sheep

Abstract: In sheep, the traditional chemical control of gastrointestinal nematode (GIN) parasites with anthelmintics has led to the widespread development of anthelmintic resistance. The selection of sheep with enhanced resistance to GIN parasites has been suggested as an alternative strategy to develop sustainable control of parasite infections. Most of the estimations of the genetic parameters for sheep resistance to GIN parasites have been obtained from young animals belonging to meat-and/or wool-specialised breeds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
2
36
1
Order By: Relevance
“…This agrees with the observations reported by Davies et al [7], who did not find any coincident QTL between parasitic traits and IgA activity. The lack of coincidence between the QTL influencing LFEC 0 and LFEC 1 , although intriguing, agrees with certain differences observed regarding the correlations between these two traits and the serum indicator traits [9]. As suggested in that work, this could be related to the limited sample period between the faecal egg counts, which could indicate that LFEC 1 is a better indicator of the initial immune response triggered by larvae at the beginning of infection.…”
Section: Discussionsupporting
confidence: 79%
“…This agrees with the observations reported by Davies et al [7], who did not find any coincident QTL between parasitic traits and IgA activity. The lack of coincidence between the QTL influencing LFEC 0 and LFEC 1 , although intriguing, agrees with certain differences observed regarding the correlations between these two traits and the serum indicator traits [9]. As suggested in that work, this could be related to the limited sample period between the faecal egg counts, which could indicate that LFEC 1 is a better indicator of the initial immune response triggered by larvae at the beginning of infection.…”
Section: Discussionsupporting
confidence: 79%
“…Higher heritability estimates for length of adult Teladorsagia circumcincta , a highly prevalent sheep nematode, than for worm number (0·62 ± 0·20 vs. 0·14 ± 0·10) suggest that variation in lamb FEC is due to variation in regulation of T. circumcincta length (and therefore fecundity) rather than ability to kill worms . This reduction in worm length is associated with a significantly heritable parasite‐specific IgA response . An important outcome of selection experiments is that selection of sheep for resistance to Haemonchus contortus , an abomasal parasite, enhances resistance to Trichostrongylus colubriformis , an intestinal parasite, due to a positive genetic correlation between resistance to them .…”
Section: Interindividual Variationmentioning
confidence: 99%
“…The QTL on OAR4 and OAR20 were confirmed by different variants of the RHM method, whereas a QTL on OAR20 positioned in the MHC region was identified as the most significant result. In relation to the result on OAR14, it is worth mentioning that a previous study had reported a significant selection sweep in the same region (40.1-55 Mb according to the OAR v2.0) of OAR14 (Fariello et al, 2013) and the QTL region (42)(43)(44)(45)(46)(47)(48)(49) to the Oar_v3.1) reported by Riggio et al (2014). Based on the multi-locus haplotypes identified in that selection sweep region by Fariello et al (2013), two possible candidate genes had been identified, the IRF3 (interferon regulatory factor 3) gene and the TGF-B1…”
Section: Detection Of Qtl Based On Whole Genome Scansmentioning
confidence: 84%
“…In the last decades there have been many studies focused on improving our understanding about the genetic determinism of parasite resistance in sheep, including studies focused on: (i) the estimation and assessment of genetic parameters of indicator traits Morris et al, 2004;Gutiérrez-Gil et al, 2010), (ii) the genetic variability and the role of some candidate genes (Sayers et al, 2005a;Benavides et al, 2002Benavides et al, , 2009, and (iii) the scanning of the genome to identify regions underlying the variation observed in the indicator traits , Gutiérrez-Gil et al, 2009bSallé et al, 2012). We provide below a brief overview of the results and conclusions derived from the three types of studies mentioned.…”
Section: Genetic Studies About Resistance To Gin Infections In Sheepmentioning
confidence: 99%
See 1 more Smart Citation